2021
DOI: 10.3390/biology10111156
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-Coding RNA SAMMSON Is a Regulator of Chemosensitivity and Metabolic Orientation in MCF-7 Doxorubicin-Resistant Breast Cancer Cells

Abstract: Despite improvements in therapeutic strategies for treating breast cancers, tumor relapse and chemoresistance remain major issues in patient outcomes. Indeed, cancer cells display a metabolic plasticity allowing a quick adaptation to the tumoral microenvironment and to cellular stresses induced by chemotherapy. Recently, long non-coding RNA molecules (lncRNAs) have emerged as important regulators of cellular metabolic orientation. In the present study, we addressed the role of the long non-coding RNA molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Also of interest, Xing et al proposed that overexpression of SAMMSON could promote the proliferation of TNBC cells by interacting with p53 (30). Furthermore, the study conducted by Charlotte Orre and colleagues revealed the role of SAMMSON in the metabolic adaptations leading to the development of chemoresistance in BC cells (31). In some other studies, SAMMSON was identified as a key lncRNA in the progression of malignant tumors (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest, Xing et al proposed that overexpression of SAMMSON could promote the proliferation of TNBC cells by interacting with p53 (30). Furthermore, the study conducted by Charlotte Orre and colleagues revealed the role of SAMMSON in the metabolic adaptations leading to the development of chemoresistance in BC cells (31). In some other studies, SAMMSON was identified as a key lncRNA in the progression of malignant tumors (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of SAMMSON inhibits glucose consumption (decrease in the lactate/glucose ratio) while the rate of respiration remarkably increased by modulating complex I activity, and the levels of ROS production decreased. They reveal that after silencing of SMMSON, mitochondrial replication, transcription and translation increased 11 . Xing et al revealed that overexpression of SMMSON increased triple‐negative breast cancer (TNBC) cell proliferation.…”
Section: Sammson and Tumorigenesismentioning
confidence: 99%
“…In addition, lncRNA-NEAT1 directly targets the expression of many prometastatic genes and tumor microenvironment-related genes (such as STAT3, WNT7A and VEGF-A) by interacting with miR-361, while miR-361 can inhibit tumor proliferation, invasion, stemness and paclitaxel resistance ( 40 ). Moreover, lncRNA-SAMMSON is highly expressed in doxorubicin-resistant cancer cells, resulting in metabolic recombination, reduced production of mitochondrial ROS, increased mitochondrial replication, transcription, and translation, and reduced resistance to chemotherapy ( 41 ).…”
Section: Lncrnas In Carcinogenesismentioning
confidence: 99%